En/Activist Drag: Kings Reflect on Queerness, Queens, and Questionable Masculinities. (4th July 2017) - Berbary, Lisbeth A.; Johnson, Corey W.
ABSTRACT: In recent years, media attention to drag performers has increased transforming the once-hidden leisure activity of gay men and lesbians into a publicly recognized phenomenon. Many of these representations of drag have fallen short in offering reflective illustrations of the connections among gender identity, performance, misogyny, patriarchy, and activism. In response, we find ourselves studying the gendered life experiences of drag kings to illuminate the variety of experiences that shape their gendered lives. We specifically look to our re-storied, visual, composite narratives of eight kings' experiences to show how drag functions as a context where social-political-capitalist transformation can be enacted.